Strategi Pengembangan Profesionalisme Guru Berkelanjutan melalui Refleksi dan Best Practices - Aisyah Syakirah; Pira pratiwi; Frika Fatimah Zahra; Ahmad Zainuri (Asosiasi Ilmuwan Pendidikan, Sosial, dan Humaniora Indonesia, 2026)
Teacher professionalism is a key factor in improving the quality of education, especially in the context of rapid changes that demand continuous competency development. Therefore, sustainable professional development for teachers has become an essential need. This article aims to examine strategies for developing teacher professionalism through reflection and the implementation of best practices in learning. The method used is a literature study with a descriptive qualitative approach, by analyzing various sources such as scientific journals, books, and relevant articles. The results show that reflection plays an important role as a means of self-evaluation that helps teachers continuously improve the quality of learning, while best practices provide concrete examples of effective and innovative teaching practices. Reflection enables teachers to identify strengths and weaknesses in their instructional processes, thereby encouraging continuous improvement and adaptive teaching strategies. Meanwhile, best practices serve as a reference for implementing evidence-based and student-centered learning approaches that can enhance classroom engagement and learning outcomes. The integration of reflection and best practices is proven to strengthen teachers' competencies holistically by combining critical self-assessment with proven pedagogical strategies. This synergy also supports collaborative learning among educators and encourages the sharing of effective teaching experiences. Thus, sustainable teacher professional development can be achieved through the consistent application of these strategies, ultimately contributing to improved educational quality and more effective learning environments in schools.